Injuries and terrain park feature use among snowboarders in alberta. Issue 4 (27th March 2011) - Russell, K; Meeuwisse, W H; Nettel-Aguirre, A; Emery, C A; Ruest, N; Wishart, J; Rowe, B H; Goulet, C; Hagel, B E
Abstract : Background: Snowboarding is a popular and risky winter sport. Snowboarders perform tricks on man-made features in terrain parks, which may introduce additional risk. Objective: To determine snowboard terrain park feature-specific injury rates and risk factors. Design: Case-control study with exposure estimation. Setting: A terrain park at a resort in Alberta, Canada, used for recreational and competitive snowboarding. Participants: Cases were snowboarders injured in the terrain park who presented to the ski patrol or local emergency department (ED) (n=334). Controls were non-injured snowboarders using the terrain park (n=1262). The number of snowboarder-runs in the terrain park was recorded. Participants were recruited for two winter seasons. Assessment of risk factors: Cases were identified from resort patient care records (PCRs) and ED logs. The PCRs captured demographic and environmental risk factors and injury assessment. Injured snowboarders were telephoned to determine exposure (feature used), listening to music and drugs/alcohol. Randomly selected controls were interviewed. Main outcome measurements: Overall and feature-specific injury rates (per 1000 runs) were calculated. Cases and controls were compared for risk factor prevalence using multiple logistic regressions to estimate adjusted OR (aOR) and 95% CI. Results: The overall injury rate was 0.75 injuries/1000 runs. Injury rates were highest on jumps (2.56/1000 runs), the half-pipe (2.56/1000 runs) and kickers (0.61/1000 runs). Compared with rails, the adjusted odds of injury were significantly higher on the half-pipe (aOR=9.6; 95% CI 4.8 to 19.3), jumps (aOR=4.3; 95% CI 2.7 to 6.8), mushroom (aOR=2.3; 95% CI 1.1 to 4.4) and kickers (aOR=2.0; 95% CI 1.3 to 3.1). The odds of severe injury (present to ED) versus minor injury did not differ by feature. Conclusions: The injury rates and odds of injury were highest on features that facilitate aerial maneouvers. Resorts may consider marking all features to indicate difficulty and associated injury risk.